Carrier-envelope-phase-controlled molecular dissociation by ultrashort chirped laser pulses - (:unkn) unknown (AMER PHYSICAL SOC, 2019)
We demonstrate and characterize that a carrier-envelope-offset-phase (CEP)-controlled ultrashort chirped field is an efficient and robust mechanism to modify the dissociation dynamics of molecular hydrogen. Different dissociation pathways are collectively induced and their interference contributes to the kinetic-energy release spectra. Chirping is able to efficiently manipulate the interferences of different dissociation pathways. We demonstrate a linear relationship between chirp and CEP dependent dissociation as well as directional electron localization.
Keywords: INTENSE; H-2(+); DYNAMICS; FIELDS; IONS